1994
DOI: 10.1161/01.hyp.24.5.538
|View full text |Cite
|
Sign up to set email alerts
|

Tissular expression and regulation of type 1 angiotensin II receptor subtypes by quantitative reverse transcriptase-polymerase chain reaction analysis.

Abstract: Recent studies have revealed that angiotensin II (Ang II) interacts with two pharmacologically different types of seven-transmembrane domain receptors, hence named Ang II type 1 and type 2 (AT, and AT 2 ) receptors. cDNAs for the AT, receptor have been cloned, and the existence of two receptor subtypes, AT, A and AT 1B , has been revealed in rat and mouse. This study presents a new approach for the specific quantification of AT, A and AT, B receptor mRNAs by reverse transcription and polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(96 citation statements)
references
References 48 publications
2
92
1
1
Order By: Relevance
“…These differences in AT2 receptor expression could be due, at least in part, to differences in culture conditions and in the growth state of the cells, quiescent or proliferating. Indeed, it has been shown that growth factors down-regulate the expression of AT2 but not that of AT, (Kambayashi et al, 1993), and we have detected minimal quantities of the AT2 receptor mRNA by RT-PCR in (Viswanathan et al, 1991;Llorens-Cortes et al, 1994). Both subtypes, ATIA and ATLB, have been found in the whole aorta (LlorensCortes et al, 1994) In turn, IP3 increases the release of Ca2+ from intracellular stores and diacylglycerol activates protein kinase C (Dostal et al, 1990;Sadoshima & Izumo, 1993).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These differences in AT2 receptor expression could be due, at least in part, to differences in culture conditions and in the growth state of the cells, quiescent or proliferating. Indeed, it has been shown that growth factors down-regulate the expression of AT2 but not that of AT, (Kambayashi et al, 1993), and we have detected minimal quantities of the AT2 receptor mRNA by RT-PCR in (Viswanathan et al, 1991;Llorens-Cortes et al, 1994). Both subtypes, ATIA and ATLB, have been found in the whole aorta (LlorensCortes et al, 1994) In turn, IP3 increases the release of Ca2+ from intracellular stores and diacylglycerol activates protein kinase C (Dostal et al, 1990;Sadoshima & Izumo, 1993).…”
Section: Discussionmentioning
confidence: 62%
“…They have very similar amino acid sequences, pharmacological specificities and signal transductions . It is currently unknown whether the two subtypes have different specific functions, but they have different patterns of expression in tissues (Gasc et al, 1994;Llorens-Cortes et al, 1994), suggesting that they could mediate different physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…In this disease, dose-dependent activation of intrarenal and systemic RAS has been demonstrated (15)(16)(17). AngII has some cellular effects on most tissues, mainly via AT1, that may contribute to the disease pathogenesis (11,19), and also regulates cellular immunity by acting on the proliferation of splenic lymphocytes (20). However, in a cutaneous DTH, AT1 deficiency did not alter the responsiveness, in accordance with a previous study (21), and we failed to find any difference between ␥ Ϫ/Ϫ mice with or without nephritis, suggesting that systemic RAS activation in this disease may not play a significant role in general T cell function.…”
Section: Renal Ras Activation Conducts Glomerular T Cell Responsementioning
confidence: 99%
“…In rodents, AT1 exists in two isoforms, AT1A and AT1B, regulated by two different genes. The murine AT1A is the isoform predominantly expressed in most tissues (19). AngII via AT1A triggers the proliferation of splenic lymphocytes following systemic cellular immune responses in mice (20).…”
mentioning
confidence: 99%
“…AT 1a receptors are more abundant in the kidney than AT 1b . 20 AT 1a receptors are also expressed in the liver, adrenal gland, ovary, heart, aorta, lung, testis, brain, adipose tissue and vascular smooth muscle, whereas AT 1b receptors are confined to the adrenal gland, brain and testis. 21 AT 2 receptors are highly expressed during fetal development and in newborn mammalian kidneys, with very little expression in the adult mammalian kidney.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%